2013
DOI: 10.1002/jemt.22323
|View full text |Cite
|
Sign up to set email alerts
|

TEM investigation on the microstructural evolution of hastelloy N induced by Ar+ion irradiation

Abstract: Hastelloy N alloy has been selected as the primary structure material for molten salt reactor. In this article, Hastelloy N alloy samples were irradiated to different doses at room temperature using 300 keV Ar(+) ions. The microstructural evolution was investigated by transmission electron microscopy (TEM) and energy-dispersive spectroscopy (EDS). Black dot defects emerged in sample irradiated at low dose (0.4 displacement per atom (dpa)), and they grew up with irradiation doses (0.4-2 dpa). A high density of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The lattice expansion suggests that the defects are randomly distributed and their concentration is sufficient to influence the long range order, and M. Liu et al [11] have investigated the irradiation induced microstructural evolution of Hastelloy N alloy, they found that radiation induced defects in Hastelloy N alloy are mainly small vacancy and interstitial clusters at irradiation dose below 1 dpa, resulting in the beginning of microstrain just like the present study. When irradiation dose exceeds 1 dpa, the defects grew up by absorbing the point defects, and finally evolved into the dislocation loops.…”
Section: Gixrd Analysis Of the Lattice Expansion Of Irradiated Samplessupporting
confidence: 69%
See 1 more Smart Citation
“…The lattice expansion suggests that the defects are randomly distributed and their concentration is sufficient to influence the long range order, and M. Liu et al [11] have investigated the irradiation induced microstructural evolution of Hastelloy N alloy, they found that radiation induced defects in Hastelloy N alloy are mainly small vacancy and interstitial clusters at irradiation dose below 1 dpa, resulting in the beginning of microstrain just like the present study. When irradiation dose exceeds 1 dpa, the defects grew up by absorbing the point defects, and finally evolved into the dislocation loops.…”
Section: Gixrd Analysis Of the Lattice Expansion Of Irradiated Samplessupporting
confidence: 69%
“…In recent years, the high dose, high flux ion irradiations have been considered as a useful tool to understand the basic mechanisms of irradiation damage in structural materials, especially for the evolution of the irradiation induced microstructures and properties [5][6][7][8][9][10]. M. Liu et al investigated the microstructural evolution of Hastelloy N alloy using Ar ion irradiation and observed that the black dot defects and small dislocation loops emerged at dose of 0.4 and 4 dpa respectively, and the size of those loops increased with irradiation fluence [11]. K. Liu et al reported that the size and the density of defects produced at a low irradiation dose rate were larger and higher than that at a high irradiation dose rate [12].…”
mentioning
confidence: 99%